2021
DOI: 10.1007/s00259-021-05501-1
|View full text |Cite
|
Sign up to set email alerts
|

What’s behind 68Ga-PSMA-11 uptake in primary prostate cancer PET? Investigation of histopathological parameters and immunohistochemical PSMA expression patterns

Abstract: Purpose Prostate-specific membrane antigen (PSMA-) PET has become a promising tool in staging and restaging of prostate carcinoma (PCa). However, specific primary tumour features might impact accuracy of PSMA-PET for PCa detection. We investigated histopathological parameters and immunohistochemical PSMA expression patterns on radical prostatectomy (RPE) specimens and correlated them to the corresponding 68Ga-PSMA-11-PET examinations. Methods RPE specimens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 29 publications
1
55
1
2
Order By: Relevance
“…Guidelines recommend that for low- and intermediate-risk PCa patients, a biopsy may be more appropriate than using mpMRI alone (this depends on other factors, such as high PSA, family history, and age) [ 17 , 33 ]. Our study showed that an additional 68 Ga-PSMA PET/CT could be helpful for deciding if these low- and intermediate-risk PCa patients should undergo a prostate biopsy or further management [ 34 ]. Another key finding was that low- and intermediate-risk PCa patients with a PSA ≥ 9.4 ng/ml and age ≥ 62.5 years were more likely to have a positive 68 Ga-PSMA PET/CT result.…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines recommend that for low- and intermediate-risk PCa patients, a biopsy may be more appropriate than using mpMRI alone (this depends on other factors, such as high PSA, family history, and age) [ 17 , 33 ]. Our study showed that an additional 68 Ga-PSMA PET/CT could be helpful for deciding if these low- and intermediate-risk PCa patients should undergo a prostate biopsy or further management [ 34 ]. Another key finding was that low- and intermediate-risk PCa patients with a PSA ≥ 9.4 ng/ml and age ≥ 62.5 years were more likely to have a positive 68 Ga-PSMA PET/CT result.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of cutoffs was proposed to detect significant prostate cancer, ranging from the SUVmax 3.15 to up to the SUVmax 9.1 [ 9 , 10 , 11 , 12 ]. In the current work, we applied the SUVmax of 6.6 cutoff, as previously described by Uprimny et al [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…The presence of focal uptake on PSMA-PET/CT, the standardised uptake value (SUVmax) and the maximal dimensions of PET-avid lesions have been correlated with the presence of csPCa [ 20 , 21 ]. There is a range of proposed cutoffs to detect csPCa from SUVmax 3.15 to up SUVmax 9.1 [ 22 , 23 ]; the concordance between preoperative PSMA PET/TC evaluation (SUVmax, dimension of the lesion), and definitive prostate specimen ranges from 81.2% (24) to 96% [ 24 , 25 , 26 , 27 , 28 ]. Moreover, PSMA PET/MRI seems to reduce the false positive rate of PET/CT (about 8% of cases) [ 26 ].…”
Section: Discussionmentioning
confidence: 99%